Global, regional, and national burden inequality of chronic kidney disease, 1990–2021: a systematic analysis for the global burden of disease study 2021 - Jingxun Guo; Jingxun Guo; Zhen Liu; Zhen Liu; Pengjun Wang; Heming Wu; Kai Fan; Kai Fan; Jianbo Jin; Jianbo Jin; Lan Zheng; Lan Zheng; et al. (Frontiers in Medicine)
BackgroundChronic kidney disease (CKD) is a significant global health issue, often linked to diabetes, hypertension, and glomerulonephritis. However, aggregated statistics can obscure heterogeneity across subtypes, age, gender, and regions. This study aimed to analyze global CKD trends from 1990 to 2021, focusing on age, gender, socio-demographic index (SDI), and regional variations.MethodsData were extracted from the Global Burden of Disease (GBD) 2021 database, covering prevalence, incidence, mortality, and disability-adjusted life years (DALYs). These were presented as counts per 100,000 population and age-standardized rates, with uncertainty intervals (UIs) to highlight variability. Joinpoint regression was used to assess trends over the 30-year period.ResultsIn 2021, global CKD prevalence was 359 million, with 11.13 million new cases, 1.53 million deaths, and 44.45 million DALYs—up 92, 156, 176, and 114% since 1990. While prevalence slightly declined, incidence, mortality, and DALYs increased significantly. CKD burden varied by region and age, with notable gender disparities.ConclusionThe study highlights a dramatic rise in CKD burden linked to population growth and aging, emphasizing the need for targeted treatment and effective global healthcare policies.